Targeted transcriptional profiling of the tumor microenvironment reveals lymphocyte exclusion and vascular dysfunction in metastatic osteosarcoma. (2nd September 2019) - Sorenson, Laurie; Fu, Yanfen; Hood, Tressa; Warren, Sarah; McEachron, Troy A.
ABSTRACT: Osteosarcoma (OS) is the most common bone tumor in pediatric and adolescent/young adult patients yet little is known about the microenvironment that supports this aggressive disease. We have used targeted gene expression profiling and immunohistochemistry to characterize the microenvironment of metastatic and non-metastatic OS specimens from pediatric patients exhibiting poor histologic response to chemotherapy. Our results indicate that metastatic specimens exhibit lymphocyte exclusion as T cells are confined to the periphery of the pulmonary lesions. Furthermore, our data provides evidence of vascular dysfunction in metastatic OS indicated by increased expression of VEGFA, an increased ANGPT2:ANGPT1 gene expression ratio, and decreased expression of SELE, the gene encoding the adhesion molecule E-selectin. Moreover, correlation analyses show an inverse relationship between lymphocyte abundance and markers of vascular dysfunction exclusively in the metastatic specimens. Together, our data shows that the non-metastatic OS specimens demonstrate increased expression of various immunotherapeutic targets in comparison metastatic specimens and identifies vascular dysfunction and lymphocyte exclusion as important processes for therapeutic intervention in metastatic disease.